Robust support vector regression model in the presence of outliers and leverage points - Dhhan, Waleed; Midi, Habshah; Alameer, Thaera (Canadian Center of Science and Education, 2017)
Support vector regression is used to evaluate the linear and non-linear relationships among variables. Although it is non-parametric technique, it is still affected by outliers, because the possibility to select them as support vectors. In this article, we proposed a robust support vector regression for linear and nonlinear target functions. In order to carry out this goal, the support vector regression model with fixed parameters is used to detect and minimize the effects of abnormal points in the data set. The efficiency of the proposed method is investigated by using real and simulation examples.